The dog knight : all for one and one for all [videorecording (DVD)] - Dumas, Alexandre, 1802-1870 ([Viva Pictures], 2024)
Dogtanian, a fearless young pup and swordsman, dreams of becoming one of the King's Muskehounds. With his friendly horse Sandy and a scrappy mouse named Pip, Dogtanian leaves for Paris in search of an adventure. But when the evil Cardinal Richelieu threatens the kingdom, Dogtanian must prove once and for all he has what it takes to be a Muskehound.